PENDUGAAN POTENSI DAN TINGKAT PEMANFAATAN IKAN LAYANG (Decapterus spp) YANG TERTANGKAP DENGAN ALAT TANGKAP BAGAN PERAHU DI PERAIRAN KABUPATEN BARRU - Khusnul Khatimah Hasrun; Muhammad Natsir Nessa; Hasrun Hasrun (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2021)
Barru Regency has various potentials for capture fisheries, including small pelagic fish such as flying fish (Decapterus spp). Until now, fly fishing in Barru Regency is still open access. So it is necessary to monitor the catch per unit effort. The identification of the type of catch is done visually. Data processing through the Schaefer Model approach. The results showed that the sustainable potential of flying fish in the waters of Barru Regency, Schaefer model (1954), was 6774.59 tons, the maximum sustainable fishing effort (fMSY) was 384 units. Meanwhile, JTB for the sustainable potential of flying fish is 5419.67 tons with a maximum number of fishing effort units of 212 units / year. The status of the utilization of flying fish resources in Barru Regency waters has been categorized as dense exploitation with a high level of cultivation. Even though they have not passed the MSY and Fopt values, caution is needed in their use.